Gauguin syndrom in women in menopausal transition - Sobieszczańska, Sylwia; Połać, Ireneusz; Stetkiewicz, Tomasz (Menopause Review/Przegląd Menopauzalny, 2009)
This article is devoted the attempt of analysis and description of problems related to the changes of personality development in women in a period of menopausal transition.